Multi-centre comparison between device-independent web-browser perimetry (Melbourne Rapid Fields-web) and SITA-Faster for glaucoma - Tiang, Joyce; Vingrys, Algis J.; Lin, Sarah; Prea, Selwyn M.; Moktar, Adam Ahmed; Bank, Allan; Agar, Ashish; Kong, Yu Xiang George (Frontiers in Ophthalmology, 2025)
PurposeVisual field testing is important for glaucoma diagnosis and management, but access to standard automated perimetry can be limited in some areas due to cost or access. Melbourne Rapid Fields-web (MRF-web) perimeter is designed to address these limitations by allowing perimetry testing on the flat screen of your personal computer.MethodsThis study is a retrospective, cross-sectional study involving two locations in Australia, one in metropolitan Melbourne and one in rural Dubbo NSW. 232 patients with stable glaucoma, glaucoma suspect or normal eyes were tested with MRF-web and outcomes were compared to the most recent Humphrey Field Analyzer (HFA) 24-2 SITA Faster test. Outcomes were compared by Deming regressions, Intraclass Correlation Coefficients (ICC) and Bland-Altman methods.ResultsPatient age ranged from 21 to 92 (average 66.3, SD 16.1). Bland-Altman found a bias of -0.50dB for Mean Deviation (MD) between the two tests, with 95% Limits of Agreement (LoA) of -6.80dB to 5.80dB. Pattern Deviation (PD) had a bias of -0.58dB with 95% LoA of -5.60dB to 4.40dB. High concordance was found for MD and PD, with ICCs of 0.87 and 0.73. No significant differences were found in false positive and fixation loss rates. Test time was approximately one minute longer for MRF-web compared to SITA-Faster. Area Under the Curve of MRF and HFA are similar indicating comparable diagnostic capacity.ConclusionMRF-web produces outcomes comparable to HFA SITA-Faster. Its portability and cost-effectiveness suggest suitability as an alternative method for visual field testing where a standard perimeter is not easily accessible.